Reciprocal dynamics between patients' choice of place and how they experience video consultations: A qualitative study. (October 2021) - Lüchau, Elle C.; Jepsen, Carole; Grønning, Anette; Hvidt, Elisabeth Assing
Objective: To analyse the reciprocal dynamics between patients' choice of place and how they experience video consultations (VCs) with the general practitioner. Methods: Qualitative, semi-structured interviews with 27 Danish patients were conducted over a period of 9 months, from February to October 2020. Interviews were analysed using thematic analysis. The analysis was guided by Nelly Oudshoorn's concept of technogeography of care. Results: The following three themes were identified in the data: VC-home dynamics: balancing boundaries; VC-workplace dynamics: logistical considerations; and VC-body image dynamics: on-screen exposure. Conclusions: Taking human geography and science and technology studies as our analytical point of departure, we used the concept of technogeography of care and demonstrated how the reciprocal dynamics between patients' choice of place and how they experience VC made boundaries fluid and complex between different contexts and places, such as the home, the workplace and the clinic. These boundaries were negotiated differently by the patients depending on their need for privacy, convenience and support. Additionally, VC reconfigured patients' and general practitioners' roles, increasing patients' responsibility in securing an appropriate health care setting.